PREDIKSI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR DENGAN PENDEKATAN MULTINOMIAL LOGIT Perusahaan Manufaktur di Bursa Efek Indonesia - Siti Hayati Efi Friantin; Hermawan Adi Hardiyanto (ADVANCE, 2017)
This study aims to determine the effect of the liquidity ratio, solvency, and profitability in predicting financial distress in manufacturing companies listed on the Indonesian stock exchange on the observation period 2012-2015. Sample of 20 manufacturing companies of which 11 companies with category 0 to healthy companies, 1 company with financial distress category 1, 7 companies with financial distress categories 2, one category of companies with financial distress 3. Liquidity measured by current ratio, solvency measured by debt to equity ratio, and profitability measured by gross profit margin and net profit margin. MANOVA used to test hypothesis 1 while the Multinomial Logit is used to test the hypothesis 2. The results of this study concluded that through the different test MANOVA can know the different between a company that is not experiencing financial distress and company experiencing financial distress, through the test Multinomial Logit know that financial ratio derived from the statement of financial position and income statement significant in predicting financial distress.Keywords: liquidity, solvency, profitability, MANOVA, Multinomial Logit, Financial Distress.